2016
DOI: 10.1016/j.jtho.2016.01.016
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Comorbidity and the Simplified Comorbidity Score on Overall Survival in Non–Small Cell Lung Cancer—A Prospective Cohort Study

Abstract: In this cohort of patients with NSCLC the SCS was not a clinically significant predictor of overall survival over and above basic patient and disease factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…[5][6][7] However, reports on the impact of comorbidity on lung cancer survival are conflicting. 3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] This may partly be explained by cohort variation, as reported cohorts include large population studies with several thousands of unselected patients as *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] However, reports on the impact of comorbidity on lung cancer survival are conflicting. 3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] This may partly be explained by cohort variation, as reported cohorts include large population studies with several thousands of unselected patients as *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported from a study of 73 patients with small-cell lung cancer, when comparing SCS ranges of 0-5 points, 6-11 points and 12-17 points (p=0.54) (23). In another prospective study form Australia that included 633 patients with non-small lung cancer, a SCS >9 was not associated with a worse survival prognosis than a SCS ≤9 (hazard ratio(HR)=1.0; p=0.8) (24). In contrast, on multivariate ANTICANCER RESEARCH 37: 2693-2696 (2017) 2694 Table I.…”
Section: Discussionmentioning
confidence: 96%
“…In other studies, the SCS represented an independent prognostic factor for NSCLC as well as small-cell lung cancer (7,21) and was more informative compared with CCI to predict outcomes in patients with NSCLC (7), although this is still debated. Numerous studies reported that SCS did not provide prognostic information in patients with lung cancer (6,5). To more precisely predict the outcome of patients with lung cancer with underlying disease, more validation is required.…”
Section: All Patients -----------------------------------------------mentioning
confidence: 99%
“…As the majority of clinical trials have been performed in young and otherwise healthy people, there is insufficient knowledge regarding the efficacy and safety of drugs in elderly patients who are particularly prone to exclusion from clinical trials owing to comorbidities, coexisting multi-pharmacies or poor performance status (PS). Comorbidities are assessed using the Charlson comorbidity index (CCI) and the simplified comorbidity score (SCS) (4)(5)(6)(7). The CCI is one of the most widely used scoring systems and has been validated in a number of diseases and the SCS has been designed for lung cancer (4,7).…”
Section: Introductionmentioning
confidence: 99%